ANALISIS FAKTOR â FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN DALAM MENGUNAKAN AIR MINUM KEMASAN MEREK AKUEN DI WAMENA Oleh : Rianik Thomas - Thomas, Rianik (JI@P, 2018)
Thomas, 2018. âAnalysis of factors â factors that affect consumersatisfaction in using bottled drinking water Akuen in Wamenaâ.Management, Yapis University Papua.This study aims to determine what factors affect consumer satisfactionin using drinking water brand Akuen in Wamena. This research consist ofone variable that is : factors influencing consumer satisfaction withindicator â indicator : image factor, service factor, quality and locationfactor. Population and sample to be taken is equal to 60 people by usingrandom sampling technique of collecting data used is by interview andquestioner. Technique of collecting data used is by interview andquestioner. Technique testing instrument data used is multiple regressionanaliysis, f test, t test and coefficient of determination. The result of theresearch shows that together image, service, quality and locationinfluence to consumer decision inchoosing drinking water of brandpackaging Akuen in Wamena. This indicates that the reliable image ofdrinking water products in providing services to consumers,satisfactoryemployee services and improved drinking water quality factors desiresand strategic location is easy to reach while individually, image,service,quality and location have a positive and significant on consumersatisfaction in choosing brand bottled drinking water Akuen in Wamenathat is well known in the community and a high sense of care can increaseconsumer satisfaction in using brand drinking water Akuen in Wamena.Keywords: Analysis of factors âfactors that affect consumer satisfaction inusing bottled drinking water.